THE ROLE OF GASTRONOMICAL IDENTITY ON DESTINATION BRANDING - GÜN, Sekan (Atlas Journal, 2020)
Today the importance given into the topics of marketing and branding have gradually increased, and in this respect, various important studies about branding and marketing have been conducted on not only goods and services, but also on destinations, since the attractions a destination has and its cuisine culture and its distinctive foods and beverages are evaluated as significant elements about this destination’s branding and to attract much more tourists. Hence, every destination has its unique gastronomic identity beside its distinctive destination identity. By means of introducing this gastronomic identity to the people effectively, positive contributions could be made on the branding of the destination. Within the scope of this study, the role and importance of gastronomic identity on destination branding was investigated. In this regard, literature review technique which is one of the qualitative research methods, was used. In the study, firstly destination and destination branding were explained, then gastronomy and gastronomic identity concepts were expressed. Furthermore, researches on the relation between destination branding and gastronomic identity in the literature were mentioned, and evaluations about the role and importance of gastronomic identity on destination branding were made. Moreover, some recommendations were made about future possible researches on study topic.